2003
DOI: 10.1034/j.1600-0609.2003.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, open, non‐comparative, phase II study of the combination of cladribine (2‐chlorodeoxyadenosine), cytarabine, and G‐CSF as induction therapy in refractory acute myeloid leukemia – a report of the Polish Adult Leukemia Group (PALG)

Abstract: CLAG regimen has significant anti-leukemic activity and an acceptable toxicity in refractory AML. The addition of 2-CdA to the first-line induction treatment may worsen the results of salvage with CLAG. The high CR rate in patients with MDS preceding AML deserves further observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 26 publications
1
35
2
1
Order By: Relevance
“…As alternative reinduction chemotherapy, CLAG [14,15] and CLAG-M [16] were respectively used in Studies 1 and 2. In the former, patients with intermediate or high cytogenetic risk and those patients requiring two induction treatments to achieve CR were qualified for allo-HSCT.…”
Section: Methodsmentioning
confidence: 99%
“…As alternative reinduction chemotherapy, CLAG [14,15] and CLAG-M [16] were respectively used in Studies 1 and 2. In the former, patients with intermediate or high cytogenetic risk and those patients requiring two induction treatments to achieve CR were qualified for allo-HSCT.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained in adults were more encouraging. In our study 2-CdA with high dose Ara-C and G-CSF (CLAG regimen) was used in refractory or relapsed AML patients, showing 50% CR rate [253]. High activity of regimen consisting of 2-CdA, Ara-C and IDA in previously untreated, elderly patients has been recently reported [254].…”
Section: Acute Leukemiasmentioning
confidence: 94%
“…2-CdA-based combination treatment was also introduced in AML patients [252][253][254][255]. The efficacy of the combination of 2-CdA and Ara-C was assessed in relapsed or refractory childhood AML, with disappointing results (no CR, 1/8 PR) [252].…”
Section: Acute Leukemiasmentioning
confidence: 99%
“…The PALG has demonstrated that CLAG is an effective therapy, achieving a CR rate of 50% in R/R AML patients [17]. Walker et al [18] conducted a study including 15 relapsed AML patients treated by CLAG, and they obtained a CR of 43.8%.…”
Section: Discussionmentioning
confidence: 99%